The Importance of Integrating Observation Data as Input to Weather Models in Europe and Indonesia During-Early the Covid-19 Pandemic - Giarno, Giarno; Muflihah, Muflihah; Manuhung, Suparman (Journal of Mathematics and Applied Statistics, 2024)
The Covid-19 pandemic that occurred throughout the world caused tremendous losses and reduced the intensity of human activities, especially in cities that had the potential to reduce the number of pollutants in the atmosphere. The purpose of this article is to see the relationship between pollutant fluctuations with weather factors and the reliability of weather models. Elaboration of pollutant data, weather models, and government policies is used to see the extent to which a decrease in pollutant concentration is detected by a weather model. The results obtained show that a decrease in pollutant intensity is very visible in almost all European cities, but for Indonesia, a significant decrease is only in Jakarta and Tangerang, while in Semarang City an increase has been detected. Sophisticated weather modeling can be used to monitor pollutant fluctuations, but this model still requires field observation data. The same condition certainly applies to other parameters, especially maritime observations for which data have not been obtained.